Accelerator programming using Directives : 5th International Workshop, WACCPD 2018, Dallas, TX, USA, November 11-17, 2018, Proceedings /: 5th International Workshop, WACCPD 2018, Dallas, TX, USA, November 11-17, 2018, Proceedings. (2019) - Unknown
No abstract available